Sites of Narrativity and Spatial Debate: Fences in Neighbourhoods in the Port of Riga - Bula, Dace (Writingplace, 2022)
Based on an ethnographic study of the neighbourhoods in the vicinity of the Port of Riga, the article examines people’s engagement with fences surrounding the territory of the port. It reacts to an observation that walls, fences and their materiality are underrepresented in research. Focusing on human engagement with the narrativity of the physical world, the article treats port’s fences as ‘storied matter’. This includes, first, an observation that these built structures constitute a narrative subject matter frequently appearing in the interviews of the lower Daugava residents. In addition, the discursivity of the Port of Riga’s fences is contemplated as constituted by their function, enforced or disputed by spatial forms of discourse (signposts, warnings, graffiti) and shaped via symbolic activities of the involved parties, which both address place-appropriation issues and transform the communicative character of these spatial objects.